Conversion and reversion of anti‐John Cunningham virus antibody serostatus: A prospective study. Issue 7 (6th June 2019) - Auer, Michael; Hegen, Harald; Sellner, Johann; Oppermann, Katrin; Bsteh, Gabriel; Di Pauli, Franziska; Berger, Thomas; Deisenhammer, Florian
Abstract: Introduction: Determination of antibodies against the John Cunningham virus (JCV) is an important tool for risk stratification in Natalizumab‐treated multiple sclerosis (MS) patients. Six‐monthly testing has been suggested for anti‐JCV antibody negative patients and patients with low antibody index in order to detect changes of serostatus. We conducted a prospective study with predefined testing intervals in order to investigate the predictability of anti‐JCV antibody status and the intervals for repetitive testing. Methods: Our study included 109 patients at the MS Clinic of the Departments of Neurology, Medical Universities of Innsbruck and Salzburg. Blood withdrawals were performed at five time points: baseline, month 1, 3, 6, and 12. Patients' sera were sent to Unilabs, Copenhagen, Denmark, where anti‐JCV antibodies were tested by a two‐step enzyme‐linked immunosorbent assay. Qualitative (negative/positive) and quantitative results (anti‐JCV antibody index) were used for statistical analyses. Results: In our cohort, 52.3% of the patients were positive for anti‐JCV antibodies at baseline, with a significant correlation with age, but no association with sex or prior disease‐modifying therapy. Seven patients converted and reverted from negative to positive status and vice versa around the cut‐off index of 0.4, but no patient showed a permanent seroconversion from negative to highly positive anti‐JCV antibody status. Conclusion: Long‐term anti‐JCV antibody status, including seroconverters/‐reverters around the cut‐off index, is highly predictable by testing three times within short intervals, however, we cannot suggest clearly defined intervals for repetitive testing. The rate of real seroconverters, i.e., new infections with JCV, per year seems lower than previously described. Abstract : We performed a prospective study, including 110 multiple sclerosis patients, with repetitive testing of anti‐John Cunningham virus (JCV) antibodies in predefined testing intervals. We were able to show that with testing of anti‐JCV antibodies three times within short‐term intervals seroconversion/‐reversion due to assay variability can be indentified early, while real seroconversion due to a new infection with JCV is rare within an observational period of 1 year.